1993
DOI: 10.1152/ajpregu.1993.264.4.r726
|View full text |Cite
|
Sign up to set email alerts
|

Organ specificity of the dopamine1 receptor/adenylyl cyclase coupling defect in spontaneously hypertensive rats

Abstract: The coupling between the dopamine1 (DA1) receptor and the G protein/adenylyl cyclase (AC) enzyme complex is defective in the proximal convoluted tubule (PCT) of 20-wk-old spontaneously hypertensive rats (SHRs). Because this coupling defect could have been due to desensitization secondary to elevated renal dopamine levels in the adult animal, we studied the interaction between DA1 receptors and AC in PCT of rats as early as 3 wk of age, a time when renal dopamine levels are similar in SHRs and their normotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 0 publications
3
56
1
Order By: Relevance
“…However, in SHR cells, this upregulation of D 1 receptors by stimulation of AT 1 receptors is lost because of decreased responsiveness of the hyperphosphorylated D 1 receptor. 46,52,53 We have reported that the renal D 1 receptor is hyperphosphorylated in SHRs as a consequence of increased activity of GRK4 54 and decreased protein phosphatase 2A activity. 49 Long-term incubation with angiotensin II decreases D 1 /AT 1 receptor coimmunoprecipitation to the same degree in cells from SHR and WKY rats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in SHR cells, this upregulation of D 1 receptors by stimulation of AT 1 receptors is lost because of decreased responsiveness of the hyperphosphorylated D 1 receptor. 46,52,53 We have reported that the renal D 1 receptor is hyperphosphorylated in SHRs as a consequence of increased activity of GRK4 54 and decreased protein phosphatase 2A activity. 49 Long-term incubation with angiotensin II decreases D 1 /AT 1 receptor coimmunoprecipitation to the same degree in cells from SHR and WKY rats.…”
Section: Discussionmentioning
confidence: 96%
“…We found that cell surface membrane expression of D 1 receptors is lower and D 1 receptor phosphorylation is higher in SHR cells than in WKY cells, although total and D 1 receptor expression are not different in the 2 cell lines. 46,54 Renal D 1 receptor phosphorylation and GRK4 activity impact on the regulation of blood pressure. Inhibition of renal GRK4 activity by antisense oligonucleotides attenuates the increase in blood pressure with age in SHRs without affecting blood pressure in WKY rats.…”
mentioning
confidence: 99%
“…This phenomenon is not due to differences in D l receptor density, D l antagonist affinity, G-proteins, effector enzyme activity per se, renal brush border Na ϩ /H ϩ exchanger or Na in the renal proximal tubules of SHR occurs as early as 3 wk of age and is receptor, organ, and nephron segment specific (18,23,24). Thus, dopamine and D l agonists stimulate adenylyl cyclase activity in the striatum and the cortical collecting duct to a similar extent in the SHR and in its normotensive control, the Wistar-Kyoto rat (WKY) (18,23,24); parathyroid hormone stimulates adenylyl cyclase activity in renal proximal tubules to a similar extent in SHR and WKY (18). Impaired transduction of the renal D 1 receptor has also been reported in another model of genetic hypertension, the Dahl salt sensitive rat (14,22).…”
Section: Introductionmentioning
confidence: 94%
“…Prior to radioligand binding the pellet was thawed on ice and washed in Dulbecco's PBS (pH 7.4) containing glucose (1 grams/liter). Radioligand binding was performed using 125 I-SCH 23982, a D 1 antagonist; non-specific binding was defined by 1 M SCH 23390 as described previously (18,20,(22)(23)(24)(25).…”
Section: Studies In Micementioning
confidence: 99%
See 1 more Smart Citation